A Meta-Analysis of the Five -Factor Model of Pesonality and Academic Performance. [article]. - Poropat, Arthur E.
This article reports a meta-analysis of personality-acedemic performance relationships, based on the 5-factor model, in which comulative sample sizes ranged over 70,000. Most analyzed studies came from the tertiary level of education, but there were similar aggregiate samples from secondary and tertiary education.There was a comparatively smaller sample derived from studies atb the primary level. Acedemic performance was found to correlate significantly with Agreeableness, Conscientiousness, and Openness. Where tested , correlations between Conscientiousness and academic perfomance were largely independent of intelligence. When secondary acedemic performance was controlled for, Conscientiousness added as much to the prediction of tertiary academic performance as did intelligence. Strong evidence was found for moderators of correlations. Academic level (primary, secondary, or tertiary), average age, of participant, and the interaction between academic level and age significantly moderated correlations with academic performance. Possible explanations for these moderator effects are discussed, and recommendations for furture research as provided. -- (from the author)